Prevalence of G6PD deficiency versus oxidizing drugs: a survey in the tertiary care hospital - Pathak, Rakesh R.; Chhaiya, Sunita B.; Mehta, Dimple S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: G6PD deficiency is distributed worldwide including India and is involved in accidental hemolysis and anemia by inadvertent use of oxidizing drugs. Awareness of community wise occurrence of G6PD deficiency can help in screening beforehand. Methods: On 150 community wise classified, non-anemic, non- hemolysed (in recent past) visitors of pathological laboratory attached to C U Shah Medical College, Surendranagar, Gujarat, Crayman’s hemoglobin colorimetric kit (item no 700540) was used to estimate normal or below normal status of G6PD. Results: 10 people (6.6% of population) were found deficient – 7 (4 male + 3 female) from Harijan community, 2 (1 male + 1 female) from Rabbari community and 1 (1 male + 0 female) from Lohana community. Conclusions: While applying oxidizing drugs in a person of Harijan community (prevalence 7 out of total 26, i.e. 27%), extra caution is required, esp. if a person otherwise vulnerable (e.g. alcoholic). For other less represented communities, larger stratified sampling is required.